2000
DOI: 10.1046/j.1469-0705.2000.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal compensatory renal hypertrophy with a unilateral functioning kidney

Abstract: Compensatory renal hypertrophy is detectable in utero and may occur as early as 22 weeks' gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 12 publications
3
28
1
3
Order By: Relevance
“…A hipertrofia compensatória tem sido observada em pacientes com rim solitário funcionante, embora o tempo e o grau da hipertrofia sejam controversos. Hill et al 25 , em estudo de 36 fetos com rim único funcionante, 22 dos quais com RDM, demonstraram que a hipertrofia renal compensatória estava presente em 44% dos casos após 29 semanas de gestação. John et al 19 , em estudo de 33 crianças com RDM, mostraram que 24% dos rins contralaterais tinham comprimentos excedendo +2 DP ao nascimento.…”
Section: Discussionunclassified
“…A hipertrofia compensatória tem sido observada em pacientes com rim solitário funcionante, embora o tempo e o grau da hipertrofia sejam controversos. Hill et al 25 , em estudo de 36 fetos com rim único funcionante, 22 dos quais com RDM, demonstraram que a hipertrofia renal compensatória estava presente em 44% dos casos após 29 semanas de gestação. John et al 19 , em estudo de 33 crianças com RDM, mostraram que 24% dos rins contralaterais tinham comprimentos excedendo +2 DP ao nascimento.…”
Section: Discussionunclassified
“…Compensatory hypertrophy has been observed in patients with a single functioning kidney, although the length and grade of the hypertrophy are controversial. Hill et al, 25 in a study of 36 fetuses with a single functioning kidney, 22 of which with MDK, demonstrated that compensatory renal hypertrophy was present in 44% of cases after 29 gestational weeks. John et al, 19 in a study of 33 children with MDK, showed that 24% of contralateral kidneys had a length that exceeded +2 SD at birth.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in affected UUA rats, severe proteinuria due to glomerular sclerosis may stress the tubular epithelium and induce interstitial infiltration, which may impair tubular concentration capacity. Enlargement of the remaining kidney has been observed in human fetuses [9,10,14] and patients [13] with a congenitally or functionally solitary kidney. In addition to being heavier than both kidneys of normal rats, the remaining right kidney in affected rats had significantly increased numbers of nephrons.…”
Section: Discussionmentioning
confidence: 99%